Kebijakan Pemerintah Kota Gorontalo Terhadap Maraknya Pembangunan Perumahan dan Alih Fungsi Lahan Pertanian (Jurnal Begawan Hukum (JBH), 2024)
This research aims to find out what the Gorontalo City Government's policy is regarding the widespread development of housing through the process of converting agricultural land. This type of research is Empirical Research. The research results show that housing development and land conversion are very important issues in urban development. The conversion of agricultural land leads to a change in the use of productive agricultural land to use of land for the construction of housing and other infrastructure. The strategies for controlling land conversion are: Ratification of Spatial Planning Regulations as well as Incentives and Disincentives. Based on the information obtained, this form of land conversion control is also carried out by means of socialization and guidance, or if developers want to build then they will be invited. Apart from that, the factor that influences whether the conversion of agricultural land is permitted is that it must be in accordance with spatial planning. The government needs to have clear and detailed spatial planning to regulate land use effectively. Good spatial planning is the key to controlling agricultural land conversion.